2017
DOI: 10.1109/map.2017.2752648
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical and Spherical Active Coated Nanoparticles as Nanoantennas: Active Nanoparticles as Nanoantennas

Abstract: In this work we review the fundamental properties of several spherical and cylindrical, passive and active, coated nano-particles (CNPs) with emphasis on their potential for nanoantenna and nano-amplifier synthesis. For the spherical geometries, the nano-particles are excited by an electric Hertzian dipole, which represents, e.g., a stimulated atom or molecule. The cylindrical nano-particles are excited by a magnetic line source. In the active cases, gain is added to the core region of the particle. For simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…Before we proceed with the results pertaining to a variety of CNRs, following remarks are in order. First, when the length of the cylindrical core-shell part of the symmetric CNR is h =∞, see Figure 1a, then the symmetric CNR goes over to a 2D cylindrical coated nano particle (CNP) investigated analytically in [26]. On the other hand, when h = 0, the symmetric CNR recovers a 3D spherical CNP studied by analytical means in [24,26].…”
Section: Solution and Quantities Of Interestmentioning
confidence: 96%
See 2 more Smart Citations
“…Before we proceed with the results pertaining to a variety of CNRs, following remarks are in order. First, when the length of the cylindrical core-shell part of the symmetric CNR is h =∞, see Figure 1a, then the symmetric CNR goes over to a 2D cylindrical coated nano particle (CNP) investigated analytically in [26]. On the other hand, when h = 0, the symmetric CNR recovers a 3D spherical CNP studied by analytical means in [24,26].…”
Section: Solution and Quantities Of Interestmentioning
confidence: 96%
“…Such a small nanometer thickness requires, however, very accurate sizedependent permittivity models of the plasmonic nanoshells. Appropriate permittivity models have been developed and used successfully for a range of nano-shell thicknesses; the specific behavior of the permittivity pertaining to a 6 nm thick Ag nano-shell used in this work can be found in e.g., [24,26]. Over the visible range of wavelengths, 450-700 nm, which is sufficient for the illustration of all results for the light-CNR interactions examined presently, the real part of the Ag permittivity is negative while its imaginary part implies a rather lossy behavior.…”
Section: The Coated Nano Rod Problem and Its Solution 21 Configuratimentioning
confidence: 99%
See 1 more Smart Citation
“…The spherical active CNP and dielectric SiO 2 constructs the proposed PI-PR models. The detail study of these material models can be found in [27][28][29][30][31] . The PI-PR models are simulated by a computational electromagnetic simulation set of tools utilizing CST Microwave Studio, which solves Maxwell's equations using frequency domain method.…”
Section: Geometry Of Antenna Model and Size Effect Drude Model This mentioning
confidence: 99%
“…Undoubtedly, electromagnetic scattering by a sphere is an archetypical testbed for physics [1], and exotic engineering conceptualization [2]. In this work, we attempt the merge between two characteristic scattering problems, i.e., scattering by a penetrable dielectric sphere and by a impenetrable surface impedance sphere.…”
Section: Introductionmentioning
confidence: 99%